Sehr schweres Differenzierungssyndrom bei Niedrigrisiko akuter Promyelozytenleukämie - eine Tücke der differenzierenden Therapie = Very severe differentiation syndrome in low risk acute promyelocytic leukemia - a peril of differentiating therapy - Hecht, Anna; Lengfelder, Eva (Deutsche medizinische Wochenschrift, 2017)
History, examinations and diagnosis: A young patient consulted the hospital because of spontaneous hematomas. The combination of pancytopenia and coagulopathy in the blood and the proving cytogenetic and moleculargenetic examinations of the bone marrow lead to the diagnosis of low-risk acute promyelocytic leukemia (APL). Therapy and clinical course: During the combination therapy with ATRA and ATO, the patient developed a severe differentiation syndrome and hyperleukocytosis. Management of the condition was only possible due to clinical expertise and massive substitution of blood products and clotting factors. Conclusion: The case illustrates the difficulty and dangers of APL induction therapy even with a favorable initial clinical presentation despite the generally low toxicity of new therapies.